STRATEGI PEMASARAN ONLINE DAN OFFLINE USAHA CEMILAN MELALUI IMPLEMENTASI BUSINESS PLAN - Nurliani Nurliani; Anni Khaerunnisa; St. Sabahannur; Sitti Rahbiah (AGRIBIOS, 2025)
Marketing is a company's function of creating, communicating, and delivering value to customers in order to manage mutually beneficial customer relationships. Entrepreneurship in the culinary sector holds great promise for a region's economic growth by creating jobs and increasing its competitiveness. Snack businesses offer good prospects for development because they don't require large capital but offer high demand. This study aims to describe online and offline product marketing and formulate a marketing mix strategy (product, price, promotion, and distribution) to increase sales volume. This research is a case study of a home industry in Makassar City, as part of the implementation of a business plan. The results show that during snack product marketing activities, the company focused on using online marketing strategies through social media platforms such as Instagram, WhatsApp, and Facebook. Online marketing successfully reached a wider consumer base, built the brand, and presented the product with attractive visual content. Digital product, pricing, distribution, and promotion strategies were implemented through discounts and free shipping. Offline marketing utilized word-of-mouth and recommendations from colleagues/friends, who served as sources of information for consumers.